Semioplastics: the Natures of Plastics - Zengiaro, Nicola (E|C, 2023)
Since the creation of plastic material, it has become pervasive in our society, directing the attention of multiple fields of research toward itself. Although semiotics has identified some meaning-making effects of plastic, there seems to have been no systematic reflection on this element. Starting with the Plasticene Lexicon (Haram et. al 2020), a semantic map of terminologies that have arisen in the scientific field in relation to plastic will be presented. A number of new terms have emerged from this research to describe unique phenomena related to the presence of plastic materials in nature. The purpose is to show the attempt to unify a vocabulary to describe a new reality of ecological systems. Then, problems concerning how plastic is figurativized, especially in relation to the realm of the microphysical, will be indicated in semiotic terms. Indeed, the materiality of plastic dissolves and seems to be unable to be grasped as a figure of speech, leading that element to make sense in the form of concept and conceptual experience. Through analysis, it will be shown how the deciphering of microplastics takes place under the sign of the invisible, showing itself only from a microscopic analysis of matter.